Effect of Chemical Challenges on the Properties of Composite Resins - Omar Geha; Luciana Tiemi Inagaki; Jaqueline Costa Favaro; Alejandra Hortencia Miranda González; Ricardo Danil Guiraldo; Murilo Baena Lopes; Sandrine Bittencourt Berger (International Journal of Dentistry)
Objective. To evaluate the chemical degradation effect on microhardness and roughness of composite resins after aging. Materials and Methods. Specimens (n = 10) were used for Filtek Z350 XT (Z350), Filtek Bulk Fill (BULK), Micerium HRI (HRI), Micerium BIOFUNCION (BIO), and Vittra APS (VITTRA). Microhardness and roughness were performed before and after degradation with the followed solutions: citric acid, phosphoric acid, 75% alcohol, and distilled water. Samples were to a 180-day chemical cycling protocol. After degradation, one sample of each group was selected for scanning electron microscope evaluation. The data were analyzed with normal distribution (Kolmogorov–Smirnov) and similarities of variations for the Bartlett test. ANOVA (two-way) followed by Tukey’s test was performed considering treatment and composite resin P<0.05. Results. For microhardness and roughness, variations were noted to different solution and resin formulations. Z350 and HRI showed higher microhardness percentage loss, and it was more evident after storage in alcohol (−48.49 ± 20.16 and −25.02 ± 14.04, respectively) and citric acid (−65.05 ± 28.97 and 16.12 ± 8.35, respectively). For roughness, Z350 and VITTRA showed less delta values after alcohol storage (−0.047 ± 0.007 and −0.022 ± 0.009, respectively). HRI had the worst roughness for citric acid (−0.090 ± 0.025). All resins were not statistically different between each other in water and phosphoric acid. Conclusion. The formulations of restorative resin materials influenced in degree of surface degradation after 180 days of chemical degradation. Water was considered the solution that causes less degradation for microhardness and roughness evaluations. For microhardness, alcohol was considered the worst solution for Z350 and HRI. For superficial roughness, Z350 and VITTRA showed less degradation in alcohol and citric and phosphoric acid solutions.